Lesson study utilization in improving the teaching competence of physical education teachers at the elementary school level - Maliza, Agnes Sopiyah; Bayu, Wahyu Indra; Yusfi, Herri (Jurnal Pendidikan Jasmani Indonesia, 2025)
This study aims to analyze the utilization of lesson study in improving the teaching competence of Physical Education (PE) teachers at the elementary school level. The lesson study process which consists of three main stages: planning, implementation, and collaborative reflection, was applied in the context of PE learning in several elementary schools. Participants in this study came from physical education teachers from the Palembang (Indonesia) area, totalling 10 elementary school PE teachers. The quality of learning is measured by looking at two aspects: teaching skills observed from recorded processes on how teachers managed the classroom and from students' formative class evaluation questionnaire after the learning process. The initial measurement and training on managing the classroom were given to the participating teachers before the lesson study was conducted. Furthermore, the lesson study program was carried out for four cycles. The same measurement was taken before and after the lesson study was concluded. All data in this study were processed using IBM SPSS 27 with paired sample t-test analysis and effect sizes. The results of the study found that lesson study at the before and after stages was proven to significantly improve the quality of teacher teaching (p<0.05), but not at the teaching skills (p>0.05). The results showed that lesson study effectively helped PE teachers identify and correct weaknesses in their teaching, improve pedagogical skills and facilitate more interactive and quality learning. In addition, lesson study also encourages the development of a collaborative culture among teachers, which contributes to improving professionalism and learning quality. This study concludes that lesson study is an effective strategy to improve the teaching competence of PE teachers at the primary school level, and it is recommended to be applied more widely in teacher development programs.